2018
DOI: 10.5194/bg-2018-478
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissolved organic matter characteristics of deciduous and coniferous forests with variable management: different at the source, aligned in the soil

Abstract: <p><strong>Abstract.</strong> Dissolved organic matter (DOM) is part of the biogeochemical cycles of carbon and nutrients, carries pollutants and drives soil formation. The DOM concentration and properties along the water flow path through forest ecosystems depend on its origin and transformation processes. To improve our understanding of the effects of forest management, especially tree species selection and management intensity, on DOM concentrations and properties o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…This pattern has largely been attributed to shifts in forest tree composition from coniferous to deciduous species (Dittman et al., 2007), since DOM composition is dependent on source material. Experiments comparing carbon quality within coniferous and deciduous forests have found that coniferous forest soils generally have higher DOC concentrations and larger, more aromatic, plant‐derived structures (Thieme et al., 2019). Furthermore, our observations of higher DOC and C2 (“lignin‐like”) fractions in spruce‐fir‐birch mineral soil solutions and stream water, highlight the importance of shallow soils in transporting relatively unprocessed OM to surface waters at high elevations (Bailey et al., 2014; Johnson et al., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern has largely been attributed to shifts in forest tree composition from coniferous to deciduous species (Dittman et al., 2007), since DOM composition is dependent on source material. Experiments comparing carbon quality within coniferous and deciduous forests have found that coniferous forest soils generally have higher DOC concentrations and larger, more aromatic, plant‐derived structures (Thieme et al., 2019). Furthermore, our observations of higher DOC and C2 (“lignin‐like”) fractions in spruce‐fir‐birch mineral soil solutions and stream water, highlight the importance of shallow soils in transporting relatively unprocessed OM to surface waters at high elevations (Bailey et al., 2014; Johnson et al., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Natural allochthonous DOM (e.g., from terrestrial soils and forests) is transported into aquatic ecosystems and contains more aromatic, complex compounds (high molecular weight DOM, HMW) with higher C to N ratios, that tend to be less bioavailable (Findlay and Sinsabaugh 2003;van den Berg et al 2012). Terrestrial DOM inputs provide a large diversity of DOM compounds that vary with vegetation type (Camino-Serrano et al 2014;Thieme et al 2019), soil type (Tank et al 2018;van den Berg et al 2012), exposure to bio-and photodegradation processes (Hernes and Benner 2003), residence time on land (Fellman et al 2013), and hydrological characteristics (Kaiser and Kalbitz 2012;Singh et al 2014;Tank et al 2018). A large fraction of this DOM is resistant to microbial consumption over shorter (monthly to annual) timescales and can accumulate through time and space in aquatic networks (Guillemette and del Giorgio 2011;Nebbioso and Piccolo 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A large fraction of this DOM is resistant to microbial consumption over shorter (monthly to annual) timescales and can accumulate through time and space in aquatic networks (Guillemette and del Giorgio 2011;Nebbioso and Piccolo 2013). These processes interact to shape the diversity of DOM and its chemical properties and bioavailability (Camino-Serrano et al 2014;Singh et al 2014;Thieme et al 2019). Therefore, changes to inputs of DOM from individual sources will impact the composition of DOM and may affect the functioning of aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…In the mineral soil, DOM concentrations are about 75% lower than that in corresponding organic layers across various climate zones and soil types, mainly because of DOM sorption to the minerals rendering the soil the first DOM sink along the water flow path through a forest ecosystem (Camino‐Serrano et al., 2014; Möller et al., 2005). The chemical DOM composition in the mineral soil appeared not to depend on the tree species, suggesting that it mainly consists of microbial degradation products (Thieme et al., 2019). Aged soil organic matter may also contribute to DOM concentrations in soil solutions, particularly at low soil moisture as detected by dating DOM with the help of the 14 C released to the atmosphere in the 1950s by nuclear weapon tests (Sanderman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%